Extraction, Physicochemical Properties, Anti-Aging, and Antioxidant Activities of Polysaccharides from Industrial Hemp Residues - Tanran Chang; Hang Li; Hongning Lv; Minghui Tan; Shoubu Hou; Xu Liu; Meng Lian; Qingsheng Zhao; Bing Zhao (Molecules, 2022)
A large amount of hemp polysaccharides remain in industrial hemp residues (IHR) after cannabidiol extraction, resulting in the waste of resources. Therefore, the systematic study of hemp polysaccharides is beneficial to the development of IHR in the future. In this study, the extraction of industrial hemp residues polysaccharide (IHRPs) was optimized by single-factor experiment and orthogonal experimental design. The optimum heating extraction conditions were extraction temperature 98 °C, solid–liquid ratio 1:10, extraction time 1 h, number of successive extractions 2, and pH at 4. The extraction ratio and the polysaccharide content were 20.12 ± 0.55% and 12.35 ± 0.26% at the conditions, respectively. Besides, the best alcohol precipitation conditions were pumping with 2 L/h, stirring continuously, and ice-water bath for 4 h. The crude IHRPs was further purified by column chromatography and the polysaccharide/protein contents of purified IHRPs were 34.44% and 1.61%. IHRPs was mainly made up of ten monosaccharides and some non-sugar components including organic acids, flavonoids, steroids, and glycoside. The FT-IR demonstrated the polysaccharide skeleton of IHRPs. Moreover, the DPPH and ABTS scavenging rate of IHRPs were 76.00% and 99.05% at the concentrations of 1 mg/mL. IHRPs could promote the epidermal cells proliferation and healing of cell scratches. Meanwhile, IHRPs could promoted the expression of anti-aging-related genes. Overall, IHRPs could be a desirable natural source of antioxidants and anti-aging products in many aspects.